Early memories of positive emotions and its relationships to attachment styles, self-compassion and psychopathology in adolescence - Cunha, Marina (2014)
Introduction: Literature has shown that early childhood experiences, especially those related to feelings of threat or safeness play a key role in emotional and social subsequent development. Objectives: (1) examine the impact of early memories of warmth and safeness on quality of attachment in adolescents; (2) Explore the relationship between early positive memories, self-compassion and psychopathology (depressive, anxiety and stress symptoms); (3) Explore the relative contribution of emotional memories and self-compassion in the prediction of depressive and anxiety symptoms. Methods: 651 adolescents (330 boys, 50.7%) aged between 12 and 18 years (M = 15.89, SD = 1.99), completed the early memories of warmth and safeness scale (EMWSS), self-compassion scale (SCS), attachment questionnaire (AQ-C) and anxiety, depression and stress scales (DASS-21). Results: Memories of warmth and safeness showed negative moderate correlations with anxiety and depressive symptoms, and positive moderate association with self-compassion. Additionally, positive emotional memories in childhood revealed adequate discriminant validity for attachment style. Adolescents classified with a secure attachment style showed significantly more early memories of warmth and safeness than those teenagers with insecure attachment (ambivalent or avoidance). Early positive memories and self-compassion have a significant and an independent contribution on the prediction of anxiety and depressive symptoms in adolescent community. Conclusions: The present study shows that the recall of emotional memories in childhood (e.g., feelings of warmth and safeness) is associated with self-compassion, as an emotion regulation process. So, these two variables may function as protective factors in the development of depressive and anxiety symptoms in adolescence.